Metabolic Phenotype and Adipose Tissue Inflammation in Patients with Chronic Obstructive Pulmonary Disease - Peter Skyba; Jozef Ukropec; Pavol Pobeha; Barbara Ukropcova; Pavol Joppa; Timea Kurdiova; Katarina Stroffekova; Miroslav Brusik; Iwar Klimes; Ivan Tkac; Daniela Gasperikova; Ruzena Tkacova (Mediators of Inflammation)
Potential links between metabolic derangements and adipose tissue (AT) inflammation in patients with chronic obstructive pulmonary disease (COPD) are unexplored. We investigated AT expressions of interleukin (IL)-6, tumor necrosis factor (TNF)-α, CD68 (macrophage cell surface receptor), caspase-3, and Bax, and their relationships to the metabolic phenotype in nine cachectic, 12 normal-weight, 12 overweight, and 11 obese patients with COPD (age 62.3±7.2 years). With increasing body mass index, increases in AT expressions of IL-6, TNF-α, and CD68 were observed (P<.001; P=.005; P<.001, resp.), in association with reduced insulin sensitivity (P<.001). No differences were observed between cachectic and normal-weight patients in AT expressions of inflammatory or proapoptotic markers. Adipose tissue CD68 and TNF-α expressions predicted insulin sensitivity independently of known confounders (P=.005; P=.025; R2=0.840). Our results suggest that AT inflammation in obese COPD patients relates to insulin resistance. Cachectic patients remain insulin sensitive, with no AT upregulation of inflammatory or proapoptotic markers.